Job Evaluation and Wage Setting in the Public Sector of Israël - Harel, Gedaliahu (Relations industrielles / Industrial Relations, 1976)
This paper examines the Israeli experience with spectoral job evaluation and incomes policy analysis, and the causes for the abortive attempt.